Stratigraphy, mammalian paleontology, paleoecology, and age correlation of the Wasatch Formation, Fossil Butte National Monument, Wyoming. (14th September 2016) - Gunnell, Gregg F.; Zonneveld, John-Paul; Bartels, William S.
Abstract: Fieldwork conducted in the Wasatch Formation in and around Fossil Butte has yielded a diverse assemblage of early Eocene vertebrates. Fossil vertebrates are distributed through three discrete stratigraphic intervals within the uppermost 180 m of the main body of the Wasatch Formation underlying the Green River Formation. These assemblages were derived primarily from fluvial overbank mudstone units overprinted with variably well-developed paleosols. The lowest (20 m) and highest (60 m) sections are characterized by less mature and more hydromorphic paleosols, whereas the middle section (100 m) is typified by more mature paleosols and more abundant channel sandstones. The combined assemblages contain at least 46 species of mammals. Faunal characteristics include high abundances of equid perissodactyls and a relatively high abundance and diversity of notharctines primates, an apparent absence of omomyid primates, relatively high rodent diversity, and relatively diverse and abundant artiodactyls. One new genus ( Eoictops new genus) and three new species ( Eoictops novaceki new species, Palaeosinopa lacus new species, and ? Notoparamys blochi new species) are included in the Fossil Butte assemblage. Also recorded are late occurrences of two hyopsodontid condylarths and an early occurrence of a rare phenacodontid condylarth. The relatively high abundances of equids and notharctines suggest that vertebrate samples were derived from relatively open paleohabitats that included forested areas along water courses. All three assemblages contain characteristic Lysitean (Wasatchian biochron Wa-6) elements, but the occurrence of the palaeotheriid perissodactyl Lambdotherium in the uppermost horizon indicates a Lostcabinian (Wa-7) age for at least the top of the Wasatch Formation. The overlying predominantly fish-bearing Fossil Butte Member of the Green River Formation also contains Lambdotherium and is therefore Wa-7 in age as well.